Discrepâncias de assentamento ocorrido em coroas totais metálicas, com e sem alívio interno, variando-se os términos cervicais e os agentes cimentantes - Figueiredo, Aldari Raimundo [UNESP] (1997)
Seating discrepancies during cementation of complete metal crowns internally relieved or not with various finishing lines and cementing agents. This study evaluated the discrepancies during cementation of complete metal crowns either relieved or not on preparation with various margin designs: chamfer, knife edge, 135 degree shoulder, 90 degree shoulder, 90 degree shoulder with 45 degree bevel. Four types of cements, three temporary and one definitive were used: 1- zinc oxide and eugenol temporary cement (Temp Bond); 2- zinc oxide and eugenol temporary cement (Provy); 3- no eugenol temporary cement (Temp Bond NE) and 4- zinc phosphate cement (S.S.White). Machined stainless dies were fabricated to resemble complete crown preparations for a lower first molar with various finishing lines. Machined stainless steel copings, either internally relieved or not were also fabricated to fit the metal dies. A controlled technique was developed to assess seating discrepancies under the horizontal metroscope. Results showed: a) the internally relieved crowns showed after cementation statistically significant reduction of marginal discrepancies regardless of cement type or margin desing; b) knife edge finishing lines showed least dicrepancies regardless of cement type followed by the 135 degree shoulder, chamfer, bevelled 90 degree shoulder and 90 degree shoulder; c) internally relieved copings with chamfer, 135 degree shoulder and knife edge finishing lines showed no statiscally significant marginal discrepancies. This indicates that any of them yields favorable results; d) regarding cements, the least marginal discrepancies were found with Temp Bond NE followed by Temp Bond, Provy and finally by the Zinc Phosphate Cement (S.S.White)